2016
DOI: 10.1002/chem.201504099
|View full text |Cite
|
Sign up to set email alerts
|

Trianguleniums as Optical Probes for G‐Quadruplexes: A Photophysical, Electrochemical, and Computational Study

Abstract: Nucleic acids can adopt non‐duplex topologies, such as G‐quadruplexes in vitro. Yet it has been challenging to establish their existence and function in vivo due to a lack of suitable tools. Recently, we identified the triangulenium compound DAOTA‐M2 as a unique fluorescence probe for such studies. This probe's emission lifetime is highly dependent on the topology of the DNA it interacts with opening up the possibility of carrying out live‐cell imaging studies. Herein, we describe the origin of its fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…Relative conformation of morpholino groups with respect to the triangulenium core of the free and CMA-bound ligand could reduce the intramolecular quenching to differed extents and may explain the enhancement in fluorescence intensity when DAOTA-M2 is bound to G-quadruplex. [6] Our current study provides structural rationale for hypothesis [6,7] that DAOTA-M2 has two different excited state lifetimes. Favorable geometric feature of DAOTA-M2 offer extensive stacking in comparison to most reported G-quadruplex ligands that cover only one or two guanines in G-quartet.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…Relative conformation of morpholino groups with respect to the triangulenium core of the free and CMA-bound ligand could reduce the intramolecular quenching to differed extents and may explain the enhancement in fluorescence intensity when DAOTA-M2 is bound to G-quadruplex. [6] Our current study provides structural rationale for hypothesis [6,7] that DAOTA-M2 has two different excited state lifetimes. Favorable geometric feature of DAOTA-M2 offer extensive stacking in comparison to most reported G-quadruplex ligands that cover only one or two guanines in G-quartet.…”
mentioning
confidence: 62%
“…[6] Thekey feature of this probe is that it shows significantly longer fluorescence lifetimes when bound to G-quadruplex DNAt han when it binds to other topologies such as duplex or single-stranded DNA. [7] With the aim of further rationalizing the behavior of DAOTA-M2 and to aid us in the development of even better and more selective triangulenium-based probes,w eh erein present detailed NMR studies to characterize the interaction between DAOTA-M2 and an intramolecular G-quadruplex DNAs tructure.W ef ocused on the modified 19-nucleotide sequence d[TAGGGAGGGTAGGGAGGGT]o riginating from the NHE III 1 region upstream of the P1 promoter of the oncogene c-myc,t he overexpression of which has been implicated in aw ide variety of human cancers. [8] This sequence contains four guanine tracts and has been shown to form aw ell-defined parallel-stranded G-quadruplex (named CMA) under physiologically relevant K + ion concentrations ( Figure 1b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction potential of DAOTA is 350 mV higher than that of ADOTA, and this chromophore should therefore be less prone to PET quenching from the phenol units, as well as it is less quenched by amino acids and DNA bases ,. To investigate this, measurements similar to those described for 3 a – 3 cPF 6 were performed on the DAOTA compounds 5 a – 5 c .…”
Section: Resultsmentioning
confidence: 99%
“…Electrophilic substitution of diazaoxatriangulenes such as 162 , for example nitration and Vilsmeier formylation, occurs on the benzene ring with two nitrogens attached, and ortho to a nitrogen . A study of the interaction of trianguleniums as optical probes for G‐quadruplexes, showed 163 to be a unique fluorescence probe . Interaction with a G‐quadruplex from the promoter region of the c‐myc oncogene revealed that they interact at 1:2 binding stoichiometry.…”
Section: Pyrido[234‐kl]acridinementioning
confidence: 99%